2016
DOI: 10.1186/s13024-016-0126-z
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of Tau antibodies for solubilized pathological Tau species but not their immunogen or insoluble Tau aggregates predicts in vivo and ex vivo efficacy

Abstract: BackgroundA few tau immunotherapies are now in clinical trials with several more likely to be initiated in the near future. A priori, it can be anticipated that an antibody which broadly recognizes various pathological tau aggregates with high affinity would have the ideal therapeutic properties. Tau antibodies 4E6 and 6B2, raised against the same epitope region but of varying specificity and affinity, were tested for acutely improving cognition and reducing tau pathology in transgenic tauopathy mice and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(119 citation statements)
references
References 46 publications
(80 reference statements)
20
99
0
Order By: Relevance
“…In later studies, we showed that tau antibodies could have the same effect [5,6], and provided various insights into the possible mechanisms of clearance [7–19]. These studies have been confirmed and extended by various groups showing benefits of immune-targeting the pS396/404 tau epitope [2,4,69,12,2027], and other tau epitopes [20,2325,2749], which as mentioned above has resulted in eight clinical trials (for a recent review of these trials see [50]), with several more likely to be initiated in the near future. We have highlighted many of these studies in some details in various reviews over the years as they have been reported so it is not necessary to elaborate further on those particular aspects (see for example [5153]).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In later studies, we showed that tau antibodies could have the same effect [5,6], and provided various insights into the possible mechanisms of clearance [7–19]. These studies have been confirmed and extended by various groups showing benefits of immune-targeting the pS396/404 tau epitope [2,4,69,12,2027], and other tau epitopes [20,2325,2749], which as mentioned above has resulted in eight clinical trials (for a recent review of these trials see [50]), with several more likely to be initiated in the near future. We have highlighted many of these studies in some details in various reviews over the years as they have been reported so it is not necessary to elaborate further on those particular aspects (see for example [5153]).…”
Section: Introductionmentioning
confidence: 89%
“…However, other features have been less studied and have sometimes led to surprising results. For example, we have shown that a low affinity antibody is more effective than a high affinity antibody against the same region [12]. However, this is a complex issue as these antibodies are likely conformational to some extent and recognize different tau species [12], which may have different degree of importance for tau pathogenesis.…”
Section: How Does It Work?mentioning
confidence: 99%
See 3 more Smart Citations